FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS PELAYANAN ASURANSI KESEHATAN DI RSUD dr. ACHMAD DIPONEGORO PUTUSSIBAU KABUPATEN KAPUAS HULU - Emiliana Henita E.21109062 (FISIP Universitas Tanjungpura, 2014)
This paper aims to investigate factors that influence service quality of health insurance at dr. Achmad Diponegoro General Hospital Putussibau in Kapuas Hulu Regency. It is a qualitative descriptive research on health insurance services at at dr. Achmad Diponegoro General Hospital Putussibau in Kapuas Hulu Regency. The research shows that health services for the cardholders have not utilized well. Time frame in completing administration record, discrimination by health workers, and slow responses to identity patients’ needs are the problems discovered in this research. This research concludes that heath services in dr. Achmad Diponegoro general hospital are not satisfactory. However, three out of five indicators of health services utilizations namely Reliability, Assurance, Tangibles, Empathy and Responsiveness has been implemented well. Reliability is the most influential factor to give best services to the patients. By this article it is suggested that dr. Achmad Diponegoro general hospital in Kapuas Hulu Regency to give the best and maximum services to all patients. Also, avoid discriminatory services practiced by paramedics and hospital staff between public and government health cover holder since they have equal right to get the best services. Key words: service quality, health insurance, health services